Employment statutes and their application towards migrant workers - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2013)
It is recognised and accepted that all workers should be treated with fairness, dignity and equality without distinction whether they are locals or migrants. There are many employment statutes enforced in Malaysia which are applicable to all workers including migrant workers, unless the legislature expressly excluded its application to certain classes of workers. The common law also imposes various duties on the parties to the contract of employment and this includes duty of mutual trust and confidence, duty to provide a safe work environment, duty to obey lawful directions of the employer and duty of fidelity and good faith, amongst others.The nature and purpose of the employment statutes administered in Malaysia are discussed in this chapter with special reference to its application to migrant workers.